基于多点成形的液压成形工艺关键技术的研究 - 王丽霞; 许春香; 胡美君 (Jixie chuandong)
The new technology of sheet material based on hydro-forming and multipoint-forming is introduced.Punch is replaced by liquid,and die is formed by adjusting the multipoint fundamental elements.And the accuracy of sheet metal surface contour is improved in multipoint forming technology by using the die pad.The hydraulic system,the basic body adjusting and other key technical problems is studied.The former is developed,the simulation test is carried out.